2012
DOI: 10.1063/1.3677194
|View full text |Cite
|
Sign up to set email alerts
|

Boson peak of alkali and alkaline earth silicate glasses: Influence of the nature and size of the network-modifying cation

Abstract: The influence of the size of the alkaline earth cation on the boson peak of binary metasilicate glasses, MSiO(3) (M = Mg, Ca, Sr, Ba), has been investigated from vibrational densities of states determined by inversion of low-temperature heat capacities. As given both by C(p)/T(3) and g(ω)/ω(2), the intensity of the boson peak undergoes a 7-fold increase from Mg to Ba, whereas its temperature and frequency correlatively decrease from 18 to 10 K and from 100 to 20 cm(-1), respectively. The boson peak results fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…67 using hyper-Raman spectroscopy. Based on this, Richet 68 concluded that the origin of the Boson peak in binary silicate glasses could be the result of the sum of two independent contributions, i . e ., rotational motions (liberation modes) of interconnected tetrahedral SiO 4 units and localized vibrations of the network modifier cations within oxygen cages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…67 using hyper-Raman spectroscopy. Based on this, Richet 68 concluded that the origin of the Boson peak in binary silicate glasses could be the result of the sum of two independent contributions, i . e ., rotational motions (liberation modes) of interconnected tetrahedral SiO 4 units and localized vibrations of the network modifier cations within oxygen cages.…”
Section: Discussionmentioning
confidence: 99%
“…According to their results the noted negative correlation is a general feature for amorphous systems. The value of (C p / T 3 ) max is strongly influenced by the nature and size of the network-modifying cation 55,68,74,75 . For example, Nakamura 75 classified the respective cations according to their ionic radii.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Richet has reported the low-temperature excess specific heat in binary alkali and alkaline-earth silicate glasses, indicating that the ionic radii of the alkali-metal and alkaline-earth metallic (AAEM) species are connected to the BP amplitude and position. 4) Although this study suggested that the dependence of specific heat on composition would be helpful for interpreting the characteristics of the BP, much less information is available about multicomponent and nonsilicate systems. Therefore, in this study, we use low-temperature specific-heat measurements to elucidate how a glass system or component affects BP characteristics.…”
Section: Introductionmentioning
confidence: 96%
“…This band is the so-called boson peak (BP). [1][2][3][4][5] The BP is attributed to an excess vibrational density of states (VDOS) that is larger than the VDOS predicted on the basis of the Debye model. 5) The excess VDOS also manifests itself as a low-energy excitation in Raman scattering and inelastic neutron scattering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation